The Influence of Supply Chain Digitalization on Integration and Agility in Company Performance - Ikrima, Ikrima; Santosa, Wahyuningsih; Dewayana, Triwulandari Satitidjati (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to analyze the effect of supply chain digitalization on integration and agility in company performance. Supply chain digitalization is considered a key factor in improving operational efficiency and effectiveness. This study found that supply chain digitalization has a significant positive effect on supply chain integration, as well as supply chain agility. Supply chain integration, which includes better coordination and information flow, also improves overall supply chain performance. In addition, supply chain agility, which includes the ability to respond to changes quickly and adaptively, also contributes positively to company performance. The results of this study indicate that the adoption of digital technologies in the supply chain not only improves integration and agility but also has a direct impact on improving overall company performance. This study provides insights into how digitalization can be leveraged to strengthen supply chain strategies and improve company competitiveness in the global market.